Analisis Kepatuhan Syariah Terhadap Larangan Riba dan Gharar Pada Produk Pembiayaan Murabahah di Bank Syariah Indonesia - Rizqina Faraaj; Muthia Ghassanie Julaeha; Haikal Ramadhan; Dera Meliana; Rina Khoirunnisa; Muhammad Zacky Alvian (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2026)
The development of the Islamic banking industry in Indonesia has experienced significant growth along with growing public awareness of the importance of financial transactions in accordance with sharia principles. One of the most frequently used financing methods in Islamic banking is the murabahah contract. However, in its implementation, concerns remain regarding the potential for usury and gharar elements that could affect the level of sharia compliance in this type of financing. This study aims to analyze the implementation of the murabahah contract and assess sharia compliance in preventing usury and gharar in murabahah financing products at Indonesian Islamic banks. The approach used in this study was qualitative through a literature review. Data were collected from various secondary sources, including scientific articles, books on Islamic economics, fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and regulations related to Islamic banking in Indonesia. Data analysis was conducted using a descriptive qualitative method to consider the suitability between the concept of muamalah fiqh and the practice of murabahah financing in Islamic financial institutions. The research results show that, in theory, the murabahah contract has been designed in accordance with Sharia law because it is based on a clear sale and purchase transaction in terms of the principal price and profit margin. However, in practice, several potential problems remain, such as the use of conventional interest rates as the basis for margins and the wakalah mechanism in purchasing goods, which can result in inconsistencies with the principle of bank ownership of goods. Therefore, it is necessary to strengthen Sharia supervision and increase transparency in the implementation of murabahah financing to ensure the principles of fairness, transaction clarity, and Sharia compliance.